AN IMPROVED PROTOCOL FOR NATURAL CONVECTIVE DRYING OF PUMPKIN - Semai, Hakim; Bouhdjar, Amor; Amari, Aissa (Food and Feed Research, 2021)
The most effective way to preserve agricultural product is drying. However, vegetable drying is an energy-consuming procedure. Convective drying is the mode considered in this work. The study intends to explore a new way of pumpkin drying, which reduces drying time and minimizes heat consumption. The study considers pumpkin thin slices and pumpkin samples with cubic shape. The samples were subjected to free convection airflow at different temperatures (40 °C, 46 °C, 52 °C, and 60 °C) for each run. A varying airflow temperature was also considered. Airflow velocity was generated by buoyancy forces for each temperature. Drying curves were plotted and fitted to the widely used thin-layer drying models. The modified Page model came out as the best-fitted model. The effective diffusivity coefficient was determined for each case using the slope moisture curve.  It appeared that diffusivity was high and drying time was short, for high temperature. Drying processes for slice configuration and cube configuration showed that the latter was more efficient. When applying the regime of increasing temperatures to the cubic samples, data analysis showed that effective diffusivity was higher during the third step in comparison to all the other drying temperatures and the total drying time was similar to that obtained at drying regime on high temperature. With this procedure, the final consumed energy was much less and the time was shorter.
Keywords: free airflow; energy optimization; sample configuration; vegetable; Page model; diffusivity